Pengolahan Air Limbah Domestik Menggunakan Tanaman Alisma Plantago Dalam Sistem Lahan Basah Buatan Aliran Bawah Permukaan (SSF - WETLAND) - Amalia Masturah; Lita Darmayanti; Yohanna Lilis H (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
The rapid growth of  the Indonesian  population  will  produce  more and more wastewater. Throwing domestic wastewater directly without treatment had caused the water pollution. One of simple, easy, low cost in maintenance and operation technology to decrease the pollutant in wastewater is constructed wetland. This research is aimed to know the efficiency and the best of detention time Subsurface Flow Wetland 2 levels with peat soil media and plant of Alisma plantago in treatment of domestic wastewater. The quality parameters of water that  was tested  are  pH, COD, and TSS.  Statistic calculation that was used in this research is Anova (Analysis of variance) of one way. The best efficiency for pH 31.7%, COD 82.1%  and TSS 90.3% in variance 4 with time of detention 4 days in reactor 1 and 1 day  in reactor 2. The  results showed  that the constructed wetland  2 levels  using  peat  soil media  and  plant of Alisma plantago  can  improve the quality of wastewater. Keywords: Wastewater, constructed wetland, alisma plantago.